Thử nghiệm đánh giá bản dịch "Đêm nóng nhất th kỷ" - theo mô hình dụng học chức năng của House's = An application of Huse s functional-pragmatic model of translation assessment to evaluating the Vietnamese translation "Đêm nóng nhất thế kỷ" /Phạm Thị Thủy. - Phạm, Thị Thủy.
House’s functional-pragmatic model of translation quality assessment (TQA) (1977, 1997) has generally been considered a promising one for research purposes. In this model, both the original and the translation are scientifically analyzed and compared with specific steps and clear linguistic-based criteria. In this paper, first, I will briefly introduce House’s TQA model; second, I will apply House’s model to assessing the translation “Đêm nóng nhất thế kỷ”; third, I will draw out some conclusions and suggest some implications for research into quality assessment of English-Vietnamese translations.